NILAI TAMBAH PRODUK OLAHAN NIRA KELAPAMENJADI GULA KELAPA DAN GULA SEMUT DI DESA HARGOTIRTO, KOKAP, KULON PROGO - Lestari Rahayu; Eni Istiyanti; Esti Sulistyaningsih (Universitas Muhammadiyah Purwokerto, 2019)
Coconut sap “ Nira’ is a liquid derived from coconut flowers, producer of tapped sap that then processed into coconut sugar and palm sugar. This called agro industry has located in Hargotirto, Kulon Progo, DI Yogyakarta this is a home industry. Sample this research taken by simple random sampling non proportional. The number of respondents taken as many as 60 people. Data taken trough as interview. The cost of productionof coconut sugar is more than a palm sugar for a week. The average income of a palm sugar maker is greater than coconut sugar. Palm sugar master gaints a full advantage compared to that of coconut sugar, which has suffered great losses. Value added of palm sugar is greater than coconut sugar.